1997
DOI: 10.1177/019262339702500518
|View full text |Cite
|
Sign up to set email alerts
|

Value of Historical Control Data and Other Issues Related to the Evaluation of Long-Term Rodent Carcinogenicity Studies

Abstract: One of the most important of these factors is consistency of gross necropsy and histopathology procedures, including the interpretation and classification of lesions. National Toxicology Program experimental protocols are structured to ensure that standard procedures are followed and that the data receive a thorough quality assurance and peer review before the nonneoplastic and neoplastic diagnoses are finalized (6,16,54 Other factors that may produce differences in control tumor rates from study to study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Oliveira et al, 2007) appears to be a most critical factor. Even when the same strain is used, there appear to be problems with standardization that hamper the use of historical control groups (Haseman et al, 1997). In this study, the most commonly used strains showed strong weight gain and changes in some tumor incidences that resulted in reduced survival over just one decade, which was attributed to the intentional or inadvertent selection of breeding stocks with faster growth and easier reproduction.…”
Section: Abolition Of Useless Testsmentioning
confidence: 78%
“…Oliveira et al, 2007) appears to be a most critical factor. Even when the same strain is used, there appear to be problems with standardization that hamper the use of historical control groups (Haseman et al, 1997). In this study, the most commonly used strains showed strong weight gain and changes in some tumor incidences that resulted in reduced survival over just one decade, which was attributed to the intentional or inadvertent selection of breeding stocks with faster growth and easier reproduction.…”
Section: Abolition Of Useless Testsmentioning
confidence: 78%
“…In particular, historical control data are particularly useful in the interpretation of studies with large numbers of animals and in studies with low numbers of animals (such as studies involving non-human primates) (Long and Hardisty, 2012). Historical control tumour data may also be useful for detecting rare tumours and for borderline effects (Haseman, 1995;Haseman et al, 1997). In addition, historical control data are useful when selecting and assessing the suitability of an animal model (Weber et al, 2011).…”
Section: Why It Is Important and When It Is Usedmentioning
confidence: 99%
“…Historical control data may be useful in evaluating the acceptability of the "normal" data obtained from control groups (Haseman et al, & 1997Paynter, 1984;Sumi et al, 1976;Tarone, 1982). Any departure from the norm in the control groups should be discussed in the evaluation document and taken into consideration, especially in any statistical analysis.…”
Section: Analysis and Evaluation Of Major Study Parametersmentioning
confidence: 99%